2012
DOI: 10.1177/097206341201400202
|View full text |Cite
|
Sign up to set email alerts
|

Declining Free Health Care and Rising Treatment Costs in India: An Analysis of National Sample Surveys 1986–2004

Abstract: The article focuses on trends in health-seeking behaviour of people and choosing between government and private sources, reasons for not accessing health care and the cost of treatment by examining three rounds of NSS data on health care use and morbidity pattern during 1986-87, 1995-96 and 2004. With variation across states, treatment-seeking from public providers has declined and preference for private providers has increased over the period. Although overall health-seeking behaviour has improved for both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…For both acute and chronic illnesses, dependency on private clinic/hospitals for treatment is a major concern. The ST who consulted health providers/personnel for second time for treatment, availing medicines from chemist or going to government health personnel practising in private are concern found in the study and is high in case of Indigenous ST. Gumber et al (2011) study also confirms people reporting lack of access to medical facilities especially in rural areas supporting the evidence that there is a possibility of ensuring better quality of healthcare services for poor, as the better off can possibly afford private healthcare services but not the poor (Gulati et al, 2010).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For both acute and chronic illnesses, dependency on private clinic/hospitals for treatment is a major concern. The ST who consulted health providers/personnel for second time for treatment, availing medicines from chemist or going to government health personnel practising in private are concern found in the study and is high in case of Indigenous ST. Gumber et al (2011) study also confirms people reporting lack of access to medical facilities especially in rural areas supporting the evidence that there is a possibility of ensuring better quality of healthcare services for poor, as the better off can possibly afford private healthcare services but not the poor (Gulati et al, 2010).…”
Section: Discussionsupporting
confidence: 63%
“…A study by Subramanian, Smith, and Subramanyam (2006) examined pattern of health deprivation among Indigenous population and found higher mortality, and excess of tobacco and alcohol consumption among Indigenous population than non-Indigenous population. Moreover, studies have revealed that poor healthcare behaviour and low level of health services utilisation are directly linked with services availability, quality of care and confidence in institutions among different sections of the people (Duraisamy, 2001; Gulati, Singh, Raushan, & Arundhati, 2010; Gumber & Bermen, 1997; Gumber, Dhak, & Lalitha, 2011; Islam & Tahir, 2002; Nyamongo, 2002; Raushan & Mutharayappa, 2014). Second, due to distinctive culture and means (non-availability of healthcare facilities) most of the ailments either go untreated or are addressed through other means of treatment ranging from alternative systems to home remedies to witchcraft and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A significant percentage of Indians avoid seeking treatment when they are ill due to a lack of knowledge about the importance of sickness, accessibility and financial problems. The gap between private and public healthcare has been decreased by increasing the healthcare costs and reducing the availability of free in-patient and out-patient care (Gumber, Dhak & Lalitha, 2012). User charge has negative effects on hospitalization among the poor (Prinja, Aggarwal, Kumar & Kanavos, 2012).…”
Section: Literaturementioning
confidence: 99%
“…Preference to seek treatment from private providers has increased, whereas preference to seek treatment from public providers has declined (Gumber et al, 2012). Indians receive low quality and quantity of healthcare services in the private and public sectors.…”
Section: Public and Private Healthcare Providersmentioning
confidence: 99%
“…The healthcare disparities between rural and urban areas have been a longstanding concern, and efforts to bridge this gap have been a priority for policymakers and public health experts. In recent years, the introduction of mobile health services especially lab facilities has emerged as a potential solution to improve healthcare access and delivery in rural India [ 5 ].…”
Section: Introductionmentioning
confidence: 99%